الفعل الاستراتيجي لدى المهندس التقني في التنظيم البيروقراطي - صحراوي, حمامة (جامعة الوادي - University of Eloued, 2023)
الملخص: إن مكانة المهندس التقني الجزائري في التنظيم وضمن سياق التحليل الاستراتيجي لميشال كروزيه، تظهر من خلال دوره كإطار مسير وإطار تقني، يسعى الى تحديد أهدافه كفاعل استراتيجي. يتجاوز دوره الرسمي في ظل تعقيدات التنظيم ويبني استراتيجياته عن طريق مناطق الظل التي يوسعها مع الفاعلين الاخرين الذين يدخلون ضمن قواعد اللعبة، ويشكلون في الأخير نسق فعل ملموس داخل التنظيم البيروقراطي. من هنا جاء إشكال الدراسة: ما هو الفعل الاستراتيجي للمهندس التقني في التنظيم البيروقراطي؟، وتبلورت الفرضية الأساسية كالتالي: يؤدي الفعل الاستراتيجي للمهندس التقني إلى تجاوز دوره الرسمي في التنظيم البيروقراطي.The position of the Algerian technical engineer in the organization and within the context of Michel Crozier strategic analysis appears through his role as a management Framework, and a technical framework, which seeks to define his goals as a strategic actor. Where he goes beyond his official role in light of the complexities of the organization, and builds his strategies through shadow areas that he expands with other actors those who fall within the rules of the game, and ultimately from a system of concrete act within the bureaucratic organization. Form here came the forms of the study: what is the role of the strategic action of the technical engineer within the bureaucratic organization? In addition, the basic hypothesis crystallized as follows: the technical act of the technical engineer leads to the exercise of his role in the bureaucratic organization.
دراسة ميدانية بمؤسسة قارورات الغاز -باتنة -
مقال
Keywords: الفعل الاستراتيجي ; المهندس التقني ; الدور ; نسق الفعل الملموس ; التنظيم البيروقراطي; strategic act; technical engineer; the role; system of concrete act; bureaucratic organization